Moderating role of firm age on the nexus between corporate governance and sources of finance: empirical evidence from Sri Lanka - Anandasayanan, S. (University of Jaffna, 2024)
Corporate governance and sources of finance are two critical components of a company's overall financial management and business strategy. The sources of finance are crucial for businesses, governments, and individuals to fund their activities, investments, and operations. Older firms usually have a more stable financial history, which gives them better access to various sources of finance. The objective of this study is to find out the moderating role of firm’s age on the nexus between corporate governance mechanism and sources of finance of listed companies in CSE. In order to attain this research objective, secondary data, which were taken from the 50 selected companies’ annual reports retrieved from CSE official webpage, have been used. Data garnered from these annual reports belong to the period from 2016 to 2021. To measure the corporate governance mechanism, Board size, composition of the board, CEO duality and institutional ownership were taken as explanatory variables. Whereas sources of financing are measured by debt-to-equity ratio, debt to total asset ratio and current liability to total asset ratio. To ascertain the main objective of this survey, the Hierarchical regression models were applied. In accordance with the results, board size, CEO duality and institutional ownership have significantly positive impact on sources of finance. Meanwhile the findings confirmed that firm age has the significant moderating role on the factors such as board size, CEO duality and institutional ownership. These findings depict that companies which adopt the proper corporate governance mechanism can easily access the essential sources of finance when they are in need.
Keywords: Board Size; CEO Duality; Corporate Governance; Debt to Equity Ratio; JEL Codes: M48, G18, G14